Faculdade de Filosofia, Ciências e Letras Santo Tomás de Aquino: um marco humanista na história da educação brasileira (1960 - 1980) - Santos, Maria de Lourdes Leal dos (2006)
This study analyzes the history trajectory of the Faculty of Philosophy, Science and Letter os Saint Tomas Aquino, in Uberaba, between 1960 and 1980, founded and directed by Dominican Sisters. It is confessional institution which represented greats conquests for Triângulo Mineiro and for several regions, considering its educacional philosophy, its qualify professoral corporation and its human formation, with repercussion until nowdays. The institution in detach is a reference in the history of Brazilian education. Its origin and consolidation as center of cultural irradiation is essentil to the Cristian ethics. The conceptions about human being, relationship, world and education evidenced in the evangelization act in the path, which focus on the reflective study and on the delibarate practice. In 1980 it was incorporated to the University of Uberaba. Thus, studying the formation of this institution, I get in its history, as a place of apprenticeship, as of the analysis of the documentary accumulation also with the autobiography testimony from its ex-learners and ex-teachers. The intelectual integrity of the corporation and the administration, the teach to do with dignity and respect stimulated ex-pupils to follow the legate of the Dominican Sisters. The wisdow and the pratices related to the deposition ratify that The FISTA wasn t, the FISTA is . It s still alive with the testimony made by its ex-learners.